1974
DOI: 10.1136/jnnp.37.2.181
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic seizures during cardiopulmonary bypass

Abstract: SYNOPSIS Eleven cardiac operations are reported in which there was electroencephalographic and/or clinical evidence of seizure activity during cardiopulmonary bypass (CPB). In four patients seizure activity appeared after acute episodes of cerebral ischaemia resulting from either hypotension or pump-generated emboli occurring at the beginning of CPB, or from air embolism occurring at the end of CPB when the myocardium was closed and defibrillated. In the remaining seven patients the seizures appeared to result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In this study plus four others (Branthwaite, 1972(Branthwaite, , 1973Casteneda et al, 1974;Stockard et al, 1974), seizures occurred in 21 of 900 patients. Suggested causes of neurologic deficits of any kind after cardiac surgery have included age (Tufo et al, 1970;Branthwaite, 1973;Stockard et al, 1973), atherosclerosis (Branthwaite, 1973;Stockard et al, 1973;Bojar et al, 1983), perfusion duration (Tufo et al, 1970;Branthwaite, 1973;Aberg and Kihlgren, 1977), toxins (Dobell et al, 1966;Stockard et al, 1974), metabolic changes (Fischer-Williams and Cooper, 1964), alveolar collapse (Fischer-Williams and Cooper, 1964), use of all blood primers (Branthwaite, 1973), emboli whether due to atheromata or air (Brierley, 1964;Aberg and Kihlgren, 1977;Bojar et al, 1983), and hypotension with or without decreased cardiac output (Brierley, 1964;Fischer-Williams and Cooper, 1964;Tufo et al, 1970;Castaneda et al, 1974;Bojar et al, 1983;Breuer et al, 1983). These hypotheses were formulated over a number of years and many of the factors once considered no longer seem as important.…”
Section: Special Situations Associated With Seizuresmentioning
confidence: 59%
“…In this study plus four others (Branthwaite, 1972(Branthwaite, , 1973Casteneda et al, 1974;Stockard et al, 1974), seizures occurred in 21 of 900 patients. Suggested causes of neurologic deficits of any kind after cardiac surgery have included age (Tufo et al, 1970;Branthwaite, 1973;Stockard et al, 1973), atherosclerosis (Branthwaite, 1973;Stockard et al, 1973;Bojar et al, 1983), perfusion duration (Tufo et al, 1970;Branthwaite, 1973;Aberg and Kihlgren, 1977), toxins (Dobell et al, 1966;Stockard et al, 1974), metabolic changes (Fischer-Williams and Cooper, 1964), alveolar collapse (Fischer-Williams and Cooper, 1964), use of all blood primers (Branthwaite, 1973), emboli whether due to atheromata or air (Brierley, 1964;Aberg and Kihlgren, 1977;Bojar et al, 1983), and hypotension with or without decreased cardiac output (Brierley, 1964;Fischer-Williams and Cooper, 1964;Tufo et al, 1970;Castaneda et al, 1974;Bojar et al, 1983;Breuer et al, 1983). These hypotheses were formulated over a number of years and many of the factors once considered no longer seem as important.…”
Section: Special Situations Associated With Seizuresmentioning
confidence: 59%
“…Based on the modified NOS scale, 9 in 13 studies of the adult population and 31 in 47 studies of the pediatric population scored 4 points or more, demonstrating low or moderate risks of bias. Two studies reported both the adult and pediatric population ( 14 , 15 ), and the sample size of some studies is relatively small and the reporting year is from 1974 to 2021, which may be attributed to the selection bias. The second bias derives primarily from the evaluation of outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the EEG findings were consistent with the changes associated with CAE in the bilateral cerebral hemispheres. A few reports have described EEG findings in CAE due to invasive iatrogenic or noniatrogenic etiologies, such as lung cancer (present case), lung transplantation, patent foramen ovale, esophageal cancer, or scuba diving, for example, “epileptiform electroencephalographic activities with a spike” during cardiopulmonary bypass [ 3 ], “epileptiform disturbance” during mitral valve replacement [ 4 ], “non-convulsive status epileptics” in lung transplantation [ 5 ], “focal seizure during hyperventilation” in a patient with a bronchogenic cyst [ 6 ], and “normal EEG” after scuba diving [ 7 ]. In our patient, focal spikes and diffuse slow waves were caused by CAE of noniatrogenic etiology, which consists of CAE due to invasive iatrogenic mechanism and noniatrogenic mechanisms, as reported previously.…”
Section: Discussionmentioning
confidence: 99%